Between virtue and profession: Theorising the rise of professionalised public participation practitioners. (February 2023) - Barry, Janice; Legacy, Crystal
Participatory planning practice is changing in response to the rise of specially trained public participation practitioners who intersect with but are also distinct from planners. These practitioners are increasingly being professionalised through new standards of competence defined by their industry bodies. The implications of this are not well accounted for in empirical studies of participatory planning, nor in the theoretical literature that seeks to understand both the potential and problems of more deliberative approaches to urban decision-making. In this paper, we revisit the sociological literature on the professions and use it to critically interrogate an observed tension between the 'virtues' of public participation (justice, equity and democracy) and efforts to consolidate public participation practice into a distinct profession that interacts with but also sits outside of professional planning.